2009
DOI: 10.1186/1471-2458-9-45
|View full text |Cite
|
Sign up to set email alerts
|

The effect of health and nutrition education intervention on women's postpartum beliefs and practices: a randomized controlled trial

Abstract: Background: 'Sitting month' is the Chinese tradition for postpartum customs. Available studies indicate that some of the traditional postpartum practices are potentially harmful for women's health. However, no intervention study aiming at postpartum practices has been performed. In this paper we evaluated the effect of a health and nutrition education intervention, which focused on improving postpartum dietary quality and optimal health behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
1
11

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 10 publications
4
77
1
11
Order By: Relevance
“…No presente estudo as mães das duas unidades relataram o consumo de líquidos para aumentar a produção de leite, o que é de fato necessário no período de amamentação 27 , ou seja, não é tabu. Também citaram ter feito consumo de alimentos derivados do milho.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…No presente estudo as mães das duas unidades relataram o consumo de líquidos para aumentar a produção de leite, o que é de fato necessário no período de amamentação 27 , ou seja, não é tabu. Também citaram ter feito consumo de alimentos derivados do milho.…”
Section: Discussionunclassified
“…Costa et al 23 Os tabus vêm limitar a ingestão alimentar, com isso provocar carências nutricionais e até mesmo a redução da produção do leite materno resultando no desmame precoce. Liu et al 27 encontraram em seu estudo a respeito de tabus alimentares durante o período do puerpério de 302 mulheres chinesas, que 18,21% relataram a produção insuficiente de leite, pelo fato de submeterem a sua alimentação aos tabus locais.…”
Section: Discussionunclassified
“…Her body needs to heal and recover from pregnancy and childbirth, a good postpartum care during the puerperal period is very important for her health. Several studies indicated that the incidences of postpartum health problems are high and these problems maybe have relation to traditional and unscientific behavior practices in the postpartum period (8) . The post-partum duration consists of variety of practices such as diet, hygiene and healing activities ,breast feeding, etc.…”
Section: Part іV:-breast Feeding Practices Of Puerperal Womenmentioning
confidence: 99%
“…Her body needs to heal and recover from the pregnancy and childbirth. A good postpartum care and wellbalanced diet during the postpartum period, is very important for the health of a woman 1 . Health education influences one's nutrition and health care knowledge, behavior and attitude toward postpartum practices.…”
Section: Introductionmentioning
confidence: 99%